A new porous fixation plate design using the topology optimization. (June 2021) - Murat, Fahri; Kaymaz, Irfan; Korkmaz, Ismail Hakkı
Highlights: A pioneering work on developing fixation plates with graded porosity produced by additive manufacturing. An optimum geometric form for the fixation plate obtained by topological optimization based on the finite element analysis. A functionally-graded porous structure is created for the optimum bulk plate model. For maximum stiffness, a gradual change in density of the porous plate is required. Abstract: Fixation plates are used to accelerate the biological healing process in the damaged area by providing mechanical stabilization for fractured bones. However, they may cause mechanical and biological complications such as aseptic loosening, stress shielding effect and necrosis during the treatment process. The aim of this study, therefore, was to reduce mechanical and biological complications observed in conventional plate models. For this purpose, an optimum plate geometry was obtained using the finite element based topology optimization approach. An optimum and functionally graded porous model were obtained for the plates used for transverse fractures of diaphysis in long bones. This model was combined with a functional graded porous cage structure, and thus a new generation porous implant model was proposed for fixation plates. In order to determine the performance of the optimum plate model, it was produced by additive manufacturing. Three models; i.e. conventional, optimum and porous fixation plates were statically tested, and they were compared experimentally and numerically using the finite element analysis (FEA). The porous model can be considered as the most suitable option since it requires less invasive inputs, and might lead minimum necrosis formation due to having lesser contact surface with the bone.